Hasan Onat’s Studies on Alevî Tradition and His Contribution to the Field (Journal of Alevism-Bektashism Studies, 2021)
This paper deals with the studies on the Alevi tradition of Professor Hasan Onat, who passed away on 26.09.2020, and his contribution to the field. Onat is an important academician and intellectual educated in Turkey. As a historian of Islamic Sects, he has done many academic studies on different subjects, both classical and recent, as well as contemporary, such as Shi’ism, 20th Century Shi’ism, Iranian Shi‘ism, sectarian discrimination and conflicts, supra-sectarian approach, religious understanding and change in Turkey. In addition to this, he made important contributions to the field of History of Islamic Sects by having his students do their master’s and doctoral dissertations on different subjects; for example on the sects -especially in their classical periods- such as Kharijis, Murji’ah, Zaydism, Mu’tazila, Karramiya, İsmailism, Ash’arism , Maturidism, İmamiyya, Druze and Qarmatians, on the concepts such as Mahdi, Batinıyya/ezotericism, İmamate, Rafıda and Ahl al-Bayt, on some important people such as Abu’l-Kasım al-Ka‘bi, and Djaʿfar al-Sadık and on many other topics. Onat has also written articles on many current topics such as globalization, secularization, identity, politics, religious education, family, freedoms, violence, sectarian conflicts, etc. Onat in his studies methodically emphasizes the following: Wherever there is people, there is religion; it is man who understands, lives and institutionalizes religion (texts); there is interpretation at the basis of religious formations such as sects, Sufi orders or religious communities; therefore, each of the religious understandings and institutional structures isn’t divine, but is human based; as such, none of them should be identified with religion/Islam and their members should not claim that they are themselves the only correct way of understanding religion/Islam; because these interpretations or institutionalizations are based on “time” and “place” and the connection of ideas with events that occur in different fields such as political, economic, etc.; no formation doesn’t stay as it emerged, it evolves by changing and transforming, and therefore a process is in question; so, it is necessary to try to understand a religious understanding or group by taking into account their own works/books and concepts formed according to the mentioned elements; the different religious understandings emerging with the effect of these elements listed above are an inevitable phenomenon. Therefore, it is striking that Onat put forward a sensitivity that prioritizes living together by seeing all these differences as (intellectual) wealth around the founding principles of religion. Due to the developments in the world and our country, Onat was not indifferent to the debates about the Alevi tradition; he both carried out academic studies and engaged his students in this topic. Onat has done studies on the following issues: important persons such as Ahmet Yesevi, Haci Bektash Veli; different structures such as Bektashi and Qizilbash tradition, works such as Velayetname and Buyruks, practical reflections in the field as in the case of Çorum, phenomena, concepts and symbols such as Karbala, identity discussions and identity-theology relations in the context of Alevi tradition, some debates on the Alevi tradition in the context of Religious Culture and Moral Knowledge Courses and the Presidency of Religious Affairs. He also has his students do doctorate study on Qizilbash differentiation and Buyruks. Onat also made important contributions to the field in terms of the Alevi tradition by addressing these issues with a methodical approach that he focused on sensitively in the field of History of Islamic Sects. In this article, Onat’s contribution to the field about the Alevi tradition is discussed with an emphasis on his own sensitivities.